Histeria: a Gata Borralheira do século XXI? - considerações a partir da clínica de pacientes com crises pseudo-epilépticas - Azevedo, Berta Hoffmann (2009)
This research is based on the author's clinical experience with patients who has pseudo-epileptic seizures. From the contact with such patients, started a qualitative study, with psychoanalytic theory support, which seeks to understand the psychic organization that engenders such symptoms. The diagnosis of pseudo-epileptic seizures is not among the diagnostic categories in Psychoanalysis. It is a neurological diagnosis determined by the similarity, as well as the difference of epilepsy. The differential diagnosis is reached by the video-EEG exam, which points to the non-involvement of any organic amendment that justify such symptoms. In this research, it was used clinical cases which were presented as a study of cases as well as clinical vignettes. The work of psychoanalytic listening problematized the neurological diagnosis of pseudo-epileptic seizures and sought purpose, in each case, a consistent diagnosis in Psychoanalysis. To reach a diagnosis in Psychoanalysis, it is not possible without a listening that takes in consideration the natural history of the subject. Stood out the use of the word "pseudo" in the composition of the neurological diagnosis and the weight represented by that expression to whom receives this diagnosis. To the idea of "false", suggested in the term "pseudo", argued the concept of psychic reality, used in Psychoanalysis, which involves not being called "pseudo." By the listening, the hysteria category was shown to be appropriate in the worked cases and put up a second research focus: seek to understand the hysteria "disappearance" in some psychoanalytic areas. At the end of the study, it was concluded that hysteria remains to be a diagnostic category placed in clinical and many of the treated cases as pseudo-epileptic in neurology may be understood, in Psychoanalysis, as hysteric patients